2009
DOI: 10.1080/00140130802707725
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between leisure-time energy expenditure and individual coping strategies for shift-work

Abstract: A total of 13 to 14% of European and North American workers are involved in shift work. The present aim is to explore the relationships between coping strategies adopted by shift workers and their leisure-time energy expenditure. Twenty-four female and 71 male shift workers (mean ± SD age: 37 ± 9 years) completed an adapted version of the Standard Shift-work Index (SSI), together with a leisure-time physical activity questionnaire. Predictors of age, time spent in shift work, gender, marital status and the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 52 publications
1
18
0
1
Order By: Relevance
“…In an interventional study on shift workers, overall "disengagement" coping scores from the SSI (Standard Shift-work Index) were positively related to leisure-time energy expenditure [31]. In another study lack of exercise was the lifestyle factor which strongly contributed to chronic fatigue in shift working nurses [32].…”
Section: Discussionmentioning
confidence: 99%
“…In an interventional study on shift workers, overall "disengagement" coping scores from the SSI (Standard Shift-work Index) were positively related to leisure-time energy expenditure [31]. In another study lack of exercise was the lifestyle factor which strongly contributed to chronic fatigue in shift working nurses [32].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Finn (, p. 32) observed that many shift‐workers have less tension and more relaxed pace on the night shift than during the day because of less supervision and fewer interruptions from clerical and management personnel. Further, shift‐work can be advantageous to a family's financial situation as it brings increased wages (Fullick et al, ). Overall, these findings call for improvements in the areas that are deleterious while retaining or enhancing those that are beneficial to help the industries to flourish at large.…”
Section: Review Of Literaturementioning
confidence: 99%
“…People are the most important resource; they control the other two resources, capital and technology, which are involved in economic activities. Organizations can adopt different forms of workforce flexibility strategies to maximize the potential and contribution of human resources to the organization (Fullick et al, 2009). As reviewed in detail in the next There is a considerable absence of research literature that evaluates ways in which people management practices such as workforce flexibility operate in different contexts.…”
mentioning
confidence: 99%
“…12 O consumo de bebidas alcoólicas foi analisado a partir da perEstima-se que na Europa e nos Estados Unidos 13% a 14% dos trabalhadores estão inseridos no contexto do trabalho em turnos, especialmente à noite. 2 Apesar de não haver dados oficiais com relação ao número de trabalhadores nesta modalidade no Brasil, acredita-se que este percentual seja próximo a esse valor 1 . Um dos principais problemas dessa atuação se associa ao que é imposto ao ser humano pelo trabalho executado em turnos, considerando o conflito entre sua natureza diurna e um ritmo artificial de atividade e iluminação.…”
Section: Variáveis Investigadasunclassified